A prospective study exploring the construct and predictive validity of the COM-B model for physical activity. (September 2019) - Howlett, Neil; Schulz, Joerg; Trivedi, Daksha; Troop, Nicholas; Chater, Angel
This study examined the constructs of capability, opportunity and motivation from the COM-B model and their influence on moderate-to-vigorous physical activity. Using a prospective survey design, 186 healthy adults completed measures representing the theoretical domains framework mapped to the COM-B, and moderate-to-vigorous physical activity 1 week later. The main indicators for the COM constructs were 'habits' (Capability), 'subjective norms' (Opportunity) and 'exercise self-identity' (Motivation). Motivation (77%) and moderate-to-vigorous physical activity (50%) were strongly predicted, with Capability and Motivation as key drivers of behaviour. Motivation was a strong mediator for Capability on behaviour. Future research should consider this approach for other populations and behaviours.